New aspects on prostaglandin D synthases - Urade, Y (Nihon yakurigaku zasshi, 1997)
Prostaglandin (PG) D2 is a major prostanoid produced in the central nervous system and mast cells, acting as a neuromodulator and an allergic and inflammatory mediator. PGD2 is readily dehydrated to produce PGs of the J series, such as PGJ2, delta 12-PGJ2, and 15-deoxy-delta 12, 14-PGJ2. We identified two distinct types of PGD synthase: one is glutathione independent, the lipocalin-type enzyme; and the other is glutathione-dependent, the hematopoietic enzyme. Lipocalin-type PGD synthase is localized in the central nervous system and genital organs, dominantly produced in the leptomeninges of the brain and pigmented epithelium of the retina, and is actively secreted as beta-trace into the cerebrospinal fluid and interphotoreceptor matrix, respectively. Since the enzyme binds all-trans- or 9-cis-retinoic acid with Kd of about 100 nM, it is considered to be a bifunctional protein acting as a PGD2-producing enzyme and an extracellular retinoid-transporter. Alternatively, we recently cloned the cDNA for hematopoietic PGD synthase, crystallized the recombinant enzyme, and determined the three-dimensional structure. The enzyme is the first member of the sigma class glutathione S-transferase (GST) from vertebrates and possesses a prominent cleft as the active site, which is never seen among other members of the GST family.